Cyclosporine With and Without Systemic Corticosteroids in Treatment of Alopecia Areata: A Systematic Review - Joanna Nowaczyk; Karolina Makowska; Adriana Rakowska; Mariusz Sikora; Lidia Rudnicka (Adis, Springer Healthcare, 2020)
Abstract Introduction Cyclosporine is commonly used in treatment for alopecia areata. It can be administered as a monotherapy or in combination with systemic corticosteroids, with various outcomes. Methods Efficacy of cyclosporine with and without systemic corticosteroids for alopecia areata was evaluated by a systematic review. Cochrane, EBSCOhost, Pubmed, Scopus and Web of Science databases were searched. Only studies published before January 2020 were included. Results A total of 2104 studies were initially examined, of which 14 were eligible for the systematic review. Among 340 reported cases, 213 had focal, multifocal or ophiasis form of alopecia areata, 60 were diagnosed with alopecia totalis and 67 with alopecia universalis. The mean response rate in the whole group of patients at the end of treatment was 65.00% (221/340; range 25-100%). Hair regrowth rate was higher in the group with cases of alopecia areata limited to scalp (124/165; mean 75.15%; range 40-100%) than in the cases with alopecia totalis (30/46; mean 65.22%; range 25-100%) or alopecia universalis (24/52; mean 46.15%; range 25-100%). The combined therapy with systemic corticosteroids was superior to the monotherapy (152/219; mean 69.41%; 0-80% vs. 69/121; mean 57.02%; range 6.67-100%) and had a lower recurrence rate (39/108; mean 36.11% vs. 34/46; mean 73.91%, respectively). The combined treatment with methylprednisolone was significantly more effective when compared to the cyclosporine monotherapy (124/183; mean 67.76%; range 0-80% vs. 69/121; mean 57.02%; range 6.67-100%). The mean time of treatment was 6.75 months (range 2-36). Limitations Limitations of our study were the retrospective character of included studies, differences in doses of prescribed drugs, and duration of the treatment and follow-up times. Conclusion Cyclosporine in combination with oral systemic corticosteroids is more effective than in monotherapy for severe alopecia areata.